A Porolepiform Rhipidistian from the Lower Devonian of the Canadian Arctic - H.-P. Schultze (Fossil Record, 2000)
A holoptychiid fish is described from the Lower Devonian of Arctic Canada. The new form is distinct from other holoptychiids by the presence of a large supraorbital bone and a boomerang-shaped tabular. Nasogaluakus n. gen. is the oldest and most primitive holoptychiid based on a phylogenetic analysis of porolepiforms and their closest relatives. The sequence of the genera corresponds to their stratigraphic appearance. Ein Holoptychiide aus dem Unterdevon der kanadischen Arktis wird beschrieben. Er unterscheidet sich durch ein großes Supraorbitale und die Bumerang-Form des Tabulare von allen übrigen Holoptychiiden. Nasogaluakus n. gen. ist der älteste und primitivste Holoptychiide, was durch eine phylogenetische Analyse der Porolepiformes belegt wird. Die Abfolge der Gattungen in diesem Verwandtschaftsschema stimmt mit ihrem zeitlichen Auftreten überein. doi:10.1002/mmng.20000030106